Identification of Urban Centralities Based on Multipurpose Cadastre (FIG Joint Land Administration Conference, 2025)
This article aims to demonstrate the importance of the Multipurpose Cadastre (Cadastro Territorial Multifinalitário – CTM) as a strategic tool for urban planning by identifying subcenters in the municipality of São José dos Pinhais, which is part of the Metropolitan Region of Curitiba (RMC), in the state of Paraná, Brazil. The analysis is based on the concept of subcenters proposed by Villaça (2001), defined as diversified clusters of commerce and services, smaller than the main center, which meet the same accessibility optimization requirements but are limited to part of the city. The methodology involves integrating data from the Geometric Registry (or Physical Cadastre) and the Economic Registry (also referred to as Fiscal Cadastre), using geoprocessing and Geographic Information System (GIS) tools, such as kernel density analysis, to identify areas with a high density of commercial and service establishments. According to Erba & Piumetto (2016), the correlation of economic, physical, legal, environmental, and social data of urban parcels is only possible through the transition from the traditional cadastre to the multipurpose model, which consolidates various layers of information—previously dispersed across isolated sectors of public administration—into a single georeferenced territorial base. As a result, subcenters will be identified and ranked within the municipality, providing a better understanding of urban dynamics and city transformation to support public policies related to mobility, housing, and infrastructure.